2009
DOI: 10.1590/s0004-282x2009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular neuroimaging characteristics of Brazilian patients with Parkinson's disease and mutations in PARK2 or PARK8 genes

Abstract: -Objective:To describe clinical and neuroimaging (SPECT) characteristics of Brazilian patients with Parkinson's disease (PD) and mutations in PARK2 or PARK8 genes. Method: A total of 119 patients meeting clinical criteria for PD were evaluated. Results: Of all patients studied, 13 had mutations in either PARK2 (n=9) or PARK8 genes (n=4). No statistically significant differences in clinical characteristics in both groups were seen. SPECT with [ 99m Tc] TRODAT-1 showed significant differences between patient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Ethical approvals were obtained at each centre and written informed consent taken as required. The PINK1 [9], heterozygous GB A mutation associated PD [12], Brazilian Parkin and LRRK2 patients [13], SNCA cases [14] and Italian Parkin cases [15] have been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Ethical approvals were obtained at each centre and written informed consent taken as required. The PINK1 [9], heterozygous GB A mutation associated PD [12], Brazilian Parkin and LRRK2 patients [13], SNCA cases [14] and Italian Parkin cases [15] have been reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…[3, 6, 7] Limb dystonia, choreic limb dyskinesia, early wearing-off phenomenon, and levodopa response are also described in these cases. [8, 9]…”
Section: Introductionmentioning
confidence: 99%
“…Barsottini et al 22 examined 119 patients with PD symptom onset before the age of 50 and found a 3.36% frequency of the PARK8 gene. Camargos et al 23 evaluated a sample of 202 patients with PD symptom onset before the age of 50 and found a familial case with mutation in the LRRK2 gene.…”
Section: Discussionmentioning
confidence: 99%